วิธีการตรวจสอบความง่วงจากคลื่นไฟฟ้าสมอง (MONITORING DROWSINESS BASED ON ELECTROENCEPHALOGRAM ANALYSIS) - ตันติสถิระพงษ์, สุชาดา; เสนะวงศ์, วงศ์วิทย์ (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2012)
จากหลักฐานความสูญเสียที่เกิดขึ้นทุกปี อุบัติเหตุบนถนนยังคงเป็นปัญหาสังคมมายาวนาน ความอ่อนล้า และความง่วงของคนขับรถเป็นปัจจัยสำคัญที่ทำให้มีอัตราการเสียชีวิตสูงเพราะความสามารถในการรับรู้ของคนขับรถลดลง ดังนั้นการตรวจสอบความง่วงเป็นการป้องกันการเกิดอุบัติเหตุที่สำคัญวิธีหนึ่ง งานวิจัยนี้จึงนำเสนอวิธีการตรวจสอบความง่วงจากคลื่นไฟฟ้าสมองโดยใช้ตัวกรองสัญญาณดิจิตอลแบบ Infinete Impulse Response (IIR) การคำนวณค่าพลังงานสเปกตรัม (power spectra) ของคลื่นไฟฟ้าสมอง และระบุสถานะของสัญญาณจากค่าพลังงานดังกล่าว ผลการทดลองแสดงให้เห็นว่าวิธีนี้สามารถระบุระดับการรับรู้ระหว่างหลับและตื่นได้แม่นยำ คำสำคัญ: ความง่วง คลื่นไฟฟ้าสมอง พลังงานสเปกตรัม ตัวกรองสัญญาณดิจิตัลแบบ Infinite Impluse Response (IIR) Road accidents have been a social concern for several decades as evident in the large amount of losses and damages every year. Driver’s fatigue and drowsiness is one of major reasons which yield high fatality rate because of the decline in the driver’s consciousness. Therefore, detecting driver’s drowsiness is of prime importance in preventing such accidents. This research proposes an electroencephalogram-based drowsiness estimation algorithm that combines IIR filtering, electroencephalogram (EEG) power spectra analysis and the classification based on optimal threshold. The results demonstrated that it is feasible to accurately determine the subjects’ alertness. Keywords: Drowsiness, Electroencephalogram (EEG), Power spectra analysis, Infinite Impulse Response (IIR) filter